Adenovirus tripartite leader sequence enhances translation of mRNAs late after infection. - Logan, J (1984)
A series of adenovirus type 5 variants was constructed to probe the function of the tripartite leader sequence, a 200-nucleotide, 5' noncoding sequence carried on the majority of late viral mRNAs. Recombinant plasmids were constructed that carried the major late transcriptional control region followed by portions of the tripartite leader sequence fused to the E1A coding region. These modified E1A genes were then rebuilt into intact viral chromosomes, replacing the corresponding wild-type region. The leader segments had no effect on the translation of E1A mRNAs early after infection, but the tripartite leader significantly enhanced (5-fold) the efficiency with which the mRNAs were translated late after infection.